Effect of Substituents and Stability of Transient Aluminum–Aminals in the Presence of Nucleophiles - Barrios, Francis J.; Springer, Brannon C.; Hazlitt, Robert A.; Colby, David A. (Synthesis, 2015)
Disubstituted hydroxylamines are synthesized and used to form aluminum–amide complexes. These reagents mask carbonyl groups in situ via nucleophilic addition. The stability and utility of the aluminum–aminals are presented in the context of selectively controlling nucleophilic addition on substrates with multiple carbonyl groups.
Keywords: aluminum; amides; amines; nucleophilic addition; carbonyl complexes